2014
DOI: 10.1111/hepr.12384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lifestyle‐related diseases and age on the development and progression of non‐alcoholic fatty liver disease

Abstract: Age is strongly associated with the development and progression of NASH. Type 2 DM may play the most crucial role among lifestyle-related diseases in the development and progression of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
(69 reference statements)
3
20
0
1
Order By: Relevance
“…In our results, age was also a risk factor in the progression of fibrosis. Similarly in agreement with other published data involving older groups of Japanese 39 , age is strongly associated with the development and progression of NASH 33 . However, this agreement does not preclude the observation that in children with NAFLD, steatosis is associated with advanced fibrosis as indicated in the latest published report 40 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our results, age was also a risk factor in the progression of fibrosis. Similarly in agreement with other published data involving older groups of Japanese 39 , age is strongly associated with the development and progression of NASH 33 . However, this agreement does not preclude the observation that in children with NAFLD, steatosis is associated with advanced fibrosis as indicated in the latest published report 40 .…”
Section: Discussionsupporting
confidence: 93%
“…Although non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome, the clinical association between non-alcoholic steatohepatitis (NASH), the severe version of NAFLD, and lifestyle-related diseases such as obesity, type 2 diabetes mellitus (T2DM), hypertension (HTN) and dyslipidemia has not been clarified 20 . Ethnicity and BMI were associated with the progression of fibrosis and the presence of cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained lifestyle changes need integrated multidisciplinary approaches, which provide behavioural support for weight loss and healthier lifestyle habits in patients with NAFLD . Age is strongly associated with the development and progression of liver steatosis so that early and timely articulated medical and behavioural approaches in youngsters might imply a more comprehensive understanding of information and factors involved in the onset and continuation of fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic predisposition and metabolic factors are believed to be important in NASH pathogenesis [4]. It has been found that approximately 70% of diabetic people have some form of NAFLD, and that approximately 5% to 20% of people with diabetes have cirrhosis due to NASH, while the five-year HCC rate in NASH patients is 0%–15% [3,5,6]. While liver cirrhosis secondary to hepatitis C infection is still the main cause of liver cancer and the most common indication for liver transplantation in the world, the prevalence of NAFLD and NASH-related cirrhosis and HCC will become an increasingly major health care problem in the future.…”
Section: Introductionmentioning
confidence: 99%